The Influence of Faculty Guidance, Self-Efficacy, and the Use of Artificial Intelligence on the Completion of Final Projects by Islamic Education Students at State Islamic University - Saputra, Adi; Usman, Jarjani; Agustina, Elita; Zubaidah, Zubaidah; Jannah, Miftahul (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze the influence of faculty guidance, self-efficacy, and the use of Artificial Intelligence (AI) on the acceleration of final project completion among students in the Islamic Religious Education (PAI) program at UIN Ar-Raniry in Banda Aceh. Delays in completing final projects often pose a major obstacle to timely graduation, influenced by both internal student factors and external factors. The research approach used was a mixed-methods design employing an associative-causal methodology. The population for this study consisted of PAI students at UIN Ar-Raniry who were working on their final projects (theses), a total of 490 students, with sampling conducted using proportional stratified random sampling. Data were collected through observation, documentation, and the distribution of structured questionnaires that had been tested for validity and reliability, and were then analyzed using descriptive statistical analysis. The research results partially indicate that: (1) faculty guidance has a positive and significant effect on accelerating the completion of final projects; (2) self-efficacy has a positive and significant effect on the acceleration of final project completion; and (3) the use of AI technology (such as tools for literature search, grammar checking, and data analysis) has been proven to significantly accelerate the process of students’ final project completion. Simultaneously, these three independent variables have a significant effect on the dependent variable. The findings of this study confirm that the integration of academic support (from faculty members), mental readiness (self-efficacy), and the use of modern technology (AI) is a crucial formula for promoting efficiency and accelerating the completion of students’ studies at PTKIN institutions.